URGENSI PENGGOLONGAN NARAPIDANA DALAM LEMBAGA PEMASYARAKATAN - Abdullah, Rahmat Hi. (FIAT JUSTISIA, 2015)
In the new system of coaching inmates, inmate treatment is applied as a subject as well as the object. The subjects here as similarities, parallels, equally as human beings, are equal as creatures of God, both as a specific creature, capable of thinking and able to make decisions. As objects because basically there is no difference in the coaching position, the difference in coaching and not as human beings. Based on the information, the classification of prisoners according to the correctional objectives with regard to the guidance and upbringing. Guidance and education will be maximized if no classification of prisoners. For example, the classification of inmates by age. Prisoners who are still children or aged under 18 years (correctional education of children), coaching and education in contrast to older age. They got special treatment and should be fostered in childrens prisons.Keywords: Inmates, Correctional Institutions, Classification